'Of Water Drops and Atomic Nuclei: Analogies and Pursuit Worthiness in Science'. (28th June 2018) - Nyrup, Rune
Abstract: This article highlights a use of analogies in science that so far has received relatively little systematic discussion: providing reasons for pursuing a model or theory. Using the development of the liquid drop model as a test case, I critically assess two extant pursuit worthiness accounts: (i) that analogies justify pursuit by supporting plausibility arguments and (ii) that analogies can serve as a guide to potential theoretical unification. Neither of these fit the liquid drop model case. Instead, I develop an alternative account, based on the idea that analogies facilitate the transfer of a well-understood modelling strategy to a new domain. 1 Introduction 2 Case Study: The Development of the Liquid Drop Model 3 Plausibility Accounts 3.1 Bartha on plausibility and analogical inference 3.2 Plausibility and the drop analogy 4 Analogies as a Guide to Unification 5 Generative Accounts 5.1 Analogy-based modelling strategies 5.2 Did analogies play a merely generative role? 6 A New Pursuit Worthiness Account of Analogies 6.1 Transferring understanding-with through analogies 6.2 Understanding-with and the liquid drop model 7 Conclusion